Pengaruh Bahan Pelleting terhadap Perkecambahan Benih Bawang Merah (Allium cepa L.) - Rajagukguk, Sion G.; Agustiansyah, Agustiansyah; Manik, Tumiar K.; Ginting, Yohannes Cahya (JURNAL AGROTROPIKA, 2023)
Shallot is an important commodity, but their productivity in Indonesia is still low. True shallot seed (TSS) can be used because of its higher production, longer shelf life, greater resistance to disease pathogens, cheaper procurement and distribution costs, guaranteed seed quality, and high productivity potential, but it has a small shape, making it difficult to plant, so seed coating technology is needed. Seed pellets are coatings of seeds to change the shape, size, and weight of seeds. This study aims to determine the effect of pelleting techniques on shallot seeds. This research was conducted with one treatment factor, namely without pelleting, soil + CMC (carboxymethyl cellulose), soil + CMC + mycorrhizae, soil + CMC + Trichoderma, soil + CMC + dolomite, soil + CMC + humic acid, soil + AG (Arabic gum), soil + AG + mycorrhizae, soil + AG + Trichoderma, soil + AG + dolomite, soil + AG + humic acid. Each treatment was carried out with three replications, resulting in 33 experimental units, each consisting of a planting media tray with 25 seeds. The results of the study showed that the pelleting technique did not affect germination, root length, coleoptile length, fresh weight, dry weight, and seed weight. Pelleting materials had a significant effect on the emergence of plumules, with the best treatment obtained in soil + CMC + humic acid, which resulted in the fastest emergence of plumules. The conclusion of this study is that shallot seed pelleting can be applied to shallot cultivation because it does not inhibit the growth and development of shallots and can facilitate the planting of shallot seeds.